Analisis Motivasi, Disiplin Diri, Kebiasaan Belajar Atlet Mahasiswa Pelatda PON Jawa Barat 2024 - Pribadi, Aurelia Josephine Finian; Nuryadi, Nuryadi; Gumilar, Agus (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This research aims to determine and analyze the relationship between study habits motivation and self-discipline and measure the academic performance of 2024 West Java PON Pelatda Student-Athletes in sports holding training camps at the Indonesian University of Education. The research methodology used is descriptive correlation research with a survey method using instruments and questionnaires. This research involved 51 athletes as respondents who were currently taking part in the West Java PON Pelatda and were still studying. The instruments used are motivation, study habits, self-discipline, and academic performance for student-athletes, to determine the relationship between study habits and motivation and self-discipline, and to determine the level of academic achievement of Pelatda athletes using descriptive formulas of percentage, frequency, mean, and multiple correlation test analysis using spss 26. The conclusion shows that study habits correlate with motivation and self-discipline with a moderate correlation level, with an R-value of 0.546. Keywords: motivation, self-discipline, study habits, academic achievement, student-athletes